2008
DOI: 10.1108/17410380810847927
|View full text |Cite
|
Sign up to set email alerts
|

Lean manufacturing performance in China: assessment of 65 manufacturing plants

Abstract: PurposeThe purpose of this paper is to investigate the adaptation of lean production and assess its current state of practice in selected plants in electronics, telecommunication, wireless, computer, food/beverage, garment, pharmaceutical, chemical, petroleum, printing, A/C and heating, and a few others in China.Design/methodology/approachAn assessment tool is used to evaluate actual manufacturing practice related to key areas of inventory; team approach; processes; maintenance; layout/handling; suppliers; set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(126 citation statements)
references
References 8 publications
1
107
1
8
Order By: Relevance
“…A major factor to achieve this is a company's ability to effectively implement a philosophy that allows it to continually and systematically improve its processes and enhance its overall operational performance. Lean manufacturing is one of the leading philosophies used by a number of organisations worldwide to improve and enhance their overall operational performance (Taj, 2008). However, the academic literature indicates that the application of lean principles and tools in the Indian manufacturing industry, especially among SMEs, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…A major factor to achieve this is a company's ability to effectively implement a philosophy that allows it to continually and systematically improve its processes and enhance its overall operational performance. Lean manufacturing is one of the leading philosophies used by a number of organisations worldwide to improve and enhance their overall operational performance (Taj, 2008). However, the academic literature indicates that the application of lean principles and tools in the Indian manufacturing industry, especially among SMEs, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The vision creates an insight of reducing waste inside the organization and entire value chain. As prescribed by Womack and Jones (1996), the practice of lean thinking and its principles have been productively implemented to many operations and manufacturing environments (Eatock, Dixon and Young, 2009, Papadopoulou and Özbayrak, 2005, Taj, 2008, Haque and James-Moore, 2004, Chowdary and George, 2012. The vital component of a lean pattern is to control processes through administration by measuring key performances (Imaj, 1997, Taylor, 2006, Zokaei and Simons, 2006.…”
Section: Lean Manufacturingmentioning
confidence: 99%
“…When compared to other quality and operations improvement approaches, Taj (2008) found that lean manufacturing is not very common in Chinese factories while Lee et al (2011) commented that only very few companies in this country are involved in the implementation of six sigma. In the case of TQM, Yusuf et al (2007) found that its implementation in China has been extensive.…”
Section: Tqem Adoptionmentioning
confidence: 99%
“…It is commonly hypothesised in the scholarly literature that large organisations have more positive attitudes towards the implementation of quality and operations improvement approaches than small companies (McLaughlin, 2013;Taj, 2008). To explore this phenomenon within the context of TQEM, a correlation analysis was performed, the results are presented in Table 1.…”
Section: Company's Size and Implementation Of Tqemmentioning
confidence: 99%